Analyses of anatomical relationship between mandibular third molar roots and variations in lingual undercut of mandible using cone-beam computed tomography - GÖÇMEN, GÖKHAN; GARİP, HASAN; BORAHAN, MEHMET OĞUZ; ATALI, ONUR (ELSEVIER TAIWAN, 2017)
Background/purpose: Anatomical features of the lingual undercut region is a potential factor that might increase the risk of displacement of a tooth or fragment. The aim of this study was to report the normal anatomical relationship of impacted lower third molar roots to the lingual cortex and soft tissues of mandible and anatomical variations of lingual balcony in the impacted third molar region. Materials and methods: One hundred impacted third molars (54 males, 46 females) from 65 (31 men, 34 women) patients were evaluated for this study using cone-beam computed tomography. Three measurements [bone thickness, angle (Ang) 1 and Ang 2] were recorded on the coronal section slices of cone-beam computed tomography images; in these images, the impacted third molar root was closest to the lingual soft tissues. Results: The average distance between the tooth root and the lingual outer cortical bone layer (bone thickness) was 1.03 mm. The averages of Ang 1 and Ang 2 were 140.61 degrees and 153.44 degrees. Ang 1 and Ang 2 of female patients were larger than those of male patients. Conclusion: The narrow angulation of the lingual balcony region and the relationship between roots and lingual soft tissues should be noted to avoid undesirable complication of displacement of a tooth or fragment into sublingual, submandibular, and pterygomandibular spaces. There was no relation in the floor of the mouth between the position of the impacted third molar roots and different lingual undercut angulation variations. (C) 2017 Association for Dental Sciences of the Republic of China. Publishing services by Elsevier B.V.
Keywords: cone-beam computed tomography; extraction; lingual undercut; mandibular third molar; PTERYGOMANDIBULAR SPACE; PANORAMIC RADIOGRAPHY; INFRATEMPORAL FOSSA; LOCAL-ANESTHESIA; MANAGEMENT; REMOVAL; CT; DISPLACEMENT; SURGERY